ANALISIS USAHATANI DAN PEMASARAN KEDELAI VARIETAS ANJASMORO DI KABUPATEN LAMPUNG TIMUR - Dayang Berliana (Politeknik Negeri Lampung, 2018)
Soybean is the main source of vegetable protein and vegetable oil consumed widely by the people of Indonesia. Soybean as one of the legumes plants becomes the basic ingredients of many foods such as ketchup, tofu, and tempeh. The high consumption of soybean products makes the Indonesian people highly dependent on soybeans. Therefore, it is essential to carry out a research about farming analysis and marketing channel of local soybeans which has been cultivated by farmers in North Raman District. This is because the marketing of soybean crops will determine the income that will be obtained by farmers later. This study aims to determine the income, financial feasibility, and marketing channels of soybeans in North Raman District East Lampung regency. The information of the study is important as it provides a clear description of local soybean marketing in Lampung that can be useful for soybean self-sufficiency program. This study used primary and secondary data. Primary data is data obtained collected directly from the field by sampling while secondary data is data obtained from provincial and central BPS (statistic agency) offices, and related institutions. Data analysis is done by tabulating the data, calculating the income and financial feasibility, and describing marketing channel of Anjasmoro soybean variety. Cultivation of Anjasmoro soybean in North Raman Subdistrict, both through breeding or not breeding, turns out to be profitable and financially feasible to undertake. There are 3 marketing channels that are commonly used by the respondent farmers. They are channel 1, 2, and 3. Channel 1 is the channel with the flow from farmers to village-level collectors who have contracts, licensed distributors or farmers to village-level collectors who have contracts, tofu/tempeh producers; Channel 2 is the one with the flow from the farmers directly selling to the producer of tofu/tempeh; and channel 3 is the one with the flow from farmers to village collecting trader, then to retailer, then to producers of tofu/tempeh.Keywords: Anjasmoro Soybean, Income, Marketing Channels